Filsafat Idealisme dalam Pendidikan - Nurmalina, Nurmalina; Wahab, Muhbib Abdul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Idealism philosophy emphasizes the importance of the mind, soul, or spirit over material or material things. The essence of humans is their soul or spirit, which is called